ESA-EAP Model in the Teaching of Purposive Communication - Miñoza, Joemar (International Journal of Language and Literary Studies, 2022)
This research determined the acceptability of the ESA-EAP model used in the Purposive Communication teaching that the respondents perceive at Cebu Technological University-Tuburan. To obtain the data needed, the descriptive-correlational method of research was employed. Specifically, an adapted questionnaire from Technology Acceptance Model was utilized to determine the acceptability of ESA-EAP. Students’ performance was measured through selected activities. It was found that the student-respondents had a very satisfactory performance; the ESA-EAP model was perceived as very acceptable by both student and teacher respondents; the mean difference between the student respondents’ and teacher respondents’ perceived level of acceptability is not significant; the relationship between academic performance and perceived level of acceptability is not significant; and language barrier and time constraints were the minor problems encountered. It was concluded that ESA-EAP is a teaching model that upholds student-centred learning as it enhances the teaching and learning process in a facilitative manner.